Characteristic microstructure underlying the fast hydration–dehydration reaction of β-La2(SO4)3: "fine platy joints" with "loose grain boundaries". Issue 48 (30th November 2018) - Shizume, Kunihiko; Hatada, Naoyuki; Toyoura, Kazuaki; Uda, Tetsuya
Abstract : The fast hydration/dehydration (water insertion/deinsertion) reaction of β-La2 (SO4 )3 is expected to be applied to thermochemical heat storage, but its kinetics have not been well understood. Abstract : The fast hydration/dehydration (water insertion/deinsertion) reaction of β-La2 (SO4 )3 is expected to be applied to thermochemical heat storage, but its kinetics have not been well understood. In this work, we investigated the microstructure of β-La2 (SO4 )3 and its contribution to the hydration reaction rate. From specific surface area measurements and transmission electron microscopy, a unique fine microstructure that looks like platy joints in geology was found in β-La2 (SO4 )3 particles with a plate thickness of several hundred nanometers. There are "loose grain boundaries" where even nitrogen gas can diffuse. This microstructure is formed when β-La2 (SO4 )3 is synthesized through dehydration of La2 (SO4 )3 ·9H2 O. The hydration reaction rate of β-La2 (SO4 )3 was quantitatively evaluated by thermogravimetry. Based on these results, we established a reasonable mechanism for water diffusion in β-La2 (SO4 )3 : water diffuses preferentially through the "loose grain boundaries" in the "platy joints" and is taken in respective crystal grains. The surface reaction on the platy grains presumably determines the rate of the hydration reaction. It is suggested that if we can increase the total surface area of platy grains during the synthesis process of β-La2 (SO4 )3, a faster rate for the hydration reaction can be expected.